Net Community Metabolism and Seawater Carbonate Chemistry Scale Non-intuitively with Coral Cover - Page, Heather N.; Courtney, Travis A.; Collins, Andrew; De Carlo, Eric H.; Andersson, Andreas J. (Frontiers in Marine Science, 2017)
Coral cover and reef health have been declining globally as reefs face local and global stressors including higher temperature and ocean acidification (OA). Ocean warming and acidification will alter rates of benthic reef metabolism (i.e., primary production, respiration, calcification, and CaCO3 dissolution), but our understanding of community and ecosystem level responses is limited in terms of functional, spatial, and temporal scales. Furthermore, dramatic changes in coral cover and benthic metabolism could alter seawater carbonate chemistry on coral reefs, locally alleviating or exacerbating OA. This study examines how benthic metabolic rates scale with changing coral cover (0-100%), and the subsequent influence of these coral communities on seawater carbonate chemistry based on mesocosm experiments in Bermuda and Hawaii. In Bermuda, no significant differences in benthic metabolism or seawater carbonate chemistry were observed for low (40%) and high (80%) coral cover due to large variability within treatments. In contrast, significant differences were detected between treatments in Hawaii with benthic metabolic rates increasing with increasing coral cover. Observed increases in daily net community calcification and nighttime net respiration scaled proportionally with coral cover. This was not true for daytime net community organic carbon production rates, which increased the most between 0 to 20% coral cover and then less so between 20% to 100%. These differences in scaling resulted in larger diel variability in seawater carbonate chemistry as coral cover increased. To place the results of the mesocosm experiments into a broader context, in situ seawater carbon dioxide (CO2) at three reef sites in Bermuda and Hawaii were also evaluated; reefs with higher coral cover experienced a greater range of diel CO2 levels, complementing the mesocosm results. The results from this study highlight the need to consider the natural complexity of reefs and additional biological and physical factors that influence seawater carbonate chemistry on larger spatial and longer temporal scales. Coordinated efforts combining various research approaches (e.g. experiments, field studies, and models) will be required to better understand how benthic metabolism integrates across functional, spatial, and temporal scales, and for making predictions on how coral reefs will respond to climate change.